ALTERAÇÕES NA ÁREA E NO ESTOQUE DE CARBONO EM BANHADO E CAMPO CULTIVADO - Estudo de caso - Macedo, Jairo (2009)
The cultivation of the Guarapuava fields contributes to the current national records for agricultural production. In this work, was studied the use pressure on the wetlands - the last remainder of this ecosystem. Through literature and backward photointerpretation, inferred the fields using before the occupation by non-Indians and their evolution. Through auger samples and physical-chemical analysis in a segment of the river basin, were identified 72.13% of Latosols with 418,64 Mg.ha-1 of organic carbon (OC); 11.30% of Cambisols, with 264,95 Mg.ha-1 and 14.94% of soils with hydromorphic features (wetlands), which was measured in 6.84 ha, the volume of 42,380.75 m3 Histic horizon (H), with 16,07% average, resulting in 479,59 Mg. CO.ha-1, able to retain and filter about 10.000 m3 .ha-1 of water, contributing to keep the superficial water regimen, groundwater fractured basaltic substratum and guarani aquifer. The stock of CO was estimated to 1.20, 0.70 and 0.62 m deep in three compartments. Restricted to 0.20 m surface, we found 106,83, 127,89 e 301,89 Mg.CO.ha-1, demonstrating the functionality of wetlands and the aggregating effect of CO by the NTS and LNTSI in the first two, surpassing the storage levels of native dry field of 14,47 Mg.ha-1. Were got up degradation evidences of flooded soils with input not hydrophilic vegetation, changes the physicochemical and the CO depletion of the order of 68% compared with similar soils. This work verified the advancement of the production system on the wetlands and need for environmental suitability of the area, with livestock removal and interruption crops of 18.53 ha of wetlands, equivalent to 14.94% of the studyed area.